Antagonistic Test of Bacteria Producing Siderophore and Protease Enzymes from The Rhizosfer of Peanut Plants on The Growth of Pathogenic Fungus Colletotrichum gloeosporioides - Nurikhsanti, Mikiyal; Zulkifli, Lalu; Rasmi, Dewa Ayu Citra; Sedijani, Prapti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
This study aims to determine the inhibitory effect of bacterial isolates producing siderophores and protease enzymes on the growth of the pathogenic fungus Colletotrichum gloeosporioides. The initial stage of research begins with the isolation of pathogenic bacteria and fungi, and is followed by testing the production of siderophores and protease enzymes. Bacteria were isolated from the rhizosphere of peanut plants, while pathogenic fungi were isolated from large chili fruit infected with anthracnose disease taken from Jelantik Village, Central Lombok Regency. Characterization of isolates for siderophore production used the Arnow method, while the protease enzyme production test used SKIM Milk Agar media. Next, the inhibition test of bacterial isolates against pathogenic fungi was carried out using the dual culture method. Characterization of potential isolates was carried out by observing bacterial colony morphology, gram staining and biochemical tests. The results of the siderophore production test showed that there was one isolate capable of producing siderophores with the isolate code RKT2. Meanwhile, the protease enzyme production test showed that all bacterial isolates produced protease enzymes, where isolate RKT9 had the highest Proteolytic Index, namely 1.57. The two isolates showed different inhibitory test results, namely isolate RKT2 had high inhibition, while RKT9 had low inhibition. The results of the research showed that a bacterial isolate (RKT2) from the rhizosphere of peanut plants was able to inhibit the growth of the pathogenic fungus Colletotrichum gloeosporioides in the high category.